RAM Characteristics Exploration with an MVEDR Model - Consigli, Carlos Fernando (2010)
Nowadays, motor vehicle safety has gained a widespread interest. Technological breakthroughs have allowed more efficient system implementations as regards life protection elements for both passengers and pedestrians. Among them, Event Data Recorders (EDR) can be found. In this paper, we present the results of simulations performed with an MVEDR model in certain scenarios.